Effects of Exposure and Vowel Space Distribution on Phonetic Drift: Evidence from American English Learners of French. (March 2019) - Lang, Benjamin; Davidson, Lisa
Recent work by Chang has shown that even at the very earliest stages of second language (L2) acquisition, the phonetic implementation of speakers' native English phoneme categories is slightly modified by contact with L2 Korean, which is referred to as "phonetic drift." This study investigates whether rapid phonetic drift generalizes to another pairing of languages. We examined naïve American English learners of French, who were recorded producing both American English and French vowels after one and six weeks of a study abroad program in Paris. In addition, the Study Abroad group is compared with proficient American English L1 speakers of French who have been residents of Paris for at least five years, to investigate the impact of long-term use of an L2 on the vowel categories of L1. Whereas the Study Abroad group showed no evidence of phonetic drift after six weeks, the Paris Residents' American English vowel space shifted along F1 and several English vowels demonstrated clear movement toward French monolingual norms. A closer look at the high vowels provides insight into how phonetic categories are influenced both by drift and by a pressure to keep vowel categories distinct between the languages. The results are also discussed with respect to potential effects of the size of the vowel inventory and the amount of input required to cause phonetic drift.